Telas de polipropileno e de submucosa de intestino de suíno na reparação de falhas na parede abdominal de ratos (Rattus norvegicus Albinus) - Bürger, Camila Paes [UNESP] (2014)
Of the many diseases that afflict humans and animals, the abdominal wall hernias are known since antiquity. There being no ideal surgical technique or study to validate a surgical procedure on the other, the objective of this work is to evaluate the behavior of the polypropylene mesh and the membrane of porcine small intestinal submucosa in repairing faults in the abdominal wall of rats. The 48 animals were divided into two groups. The first group, the animals were divided into two subgroups with four groups of four animals each, corresponding to observation times postoperatively for membranes made of polypropylene (PP) and porcine intestinal submucosa (SIS) (7, 15, 30 and 45 days) were made and where the clinical- surgical evaluations, macroscopic clinical post mortem, histomorphometric and scanning electron microscopy. The second large group, two subgroups of 30 and 45 days with four animals each, for each biomaterial for strain evaluation. Of the two groups, both showed adhesions on the material. In the pressure test, the screen PP has proved more resistant after 30 days of observation, since the SIS mesh showed burst in the region of the suture. Both groups showed an inflammatory reaction, and the reaction in the SIS group was smaller and quicker resolution. The presence of collagen was seen in both groups with a predominance of type I collagen and SIS group was found in larger quantities since the beginning of the experiment. And the organization of the tissue was higher in the SIS screen. Concluding that the two screens are biocompatible, showing no superiority of any of the materials and suggesting the union of two screens for new jobs